Quels usages des technologies dans la reprise d’études à distance ? - Cathia Papi (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
As students have been used to face-to-face teaching, we wonder how they adapt to the socio-constructivist type of pedagogy implemented by collaborative platforms through e-learning. We carried out analyses based on activity statements and interviews with learners who suspended their education, but are now preparing to continue their education via on-line education. The use of different technologies allows us to think about the large field of e-learning practices which do not always correspond to those envisioned. We then question the point of such a technico-pedagogic model for preparing for exams based on individually evaluated restitutions of academic knowledge.